2006
DOI: 10.1158/1078-0432.ccr-05-1892
|View full text |Cite
|
Sign up to set email alerts
|

Delta-24 Increases the Expression and Activity of Topoisomerase I and Enhances the Antiglioma Effect of Irinotecan

Abstract: Purpose: In this study, we sought to determine whether Delta-24 could sensitize glioma cells to the topoisomerase I inhibitor irinotecan (CPT-11) and to identify the mechanisms underlying this enhanced anticancer effect. Experimental Design: We used human glioblastoma cell lines for the in vitro studies. The expression of topoisomerase I was determined in Western blot analyses, and topoisomerase I activity was determined by measuring the relaxation of a supercoiled DNA. The cell cycle distribution of cells was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
26
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(27 citation statements)
references
References 21 publications
1
26
0
Order By: Relevance
“…4,9,26,38,40,42,43 Here, we demonstrate that the potency of AdDD was increased in combination with both gemcitabine and irinotecan. In previous studies we found that AdD19K in PT45 and SUIT-2 cells could enhance gemcitabine-induced apoptosis and that AdDD interacted synergistically with docetaxel in prostate cancer cells.…”
Section: Discussionmentioning
confidence: 64%
See 2 more Smart Citations
“…4,9,26,38,40,42,43 Here, we demonstrate that the potency of AdDD was increased in combination with both gemcitabine and irinotecan. In previous studies we found that AdD19K in PT45 and SUIT-2 cells could enhance gemcitabine-induced apoptosis and that AdDD interacted synergistically with docetaxel in prostate cancer cells.…”
Section: Discussionmentioning
confidence: 64%
“…31 This deletion restricts replication mainly to cancer cells as demonstrated for E1ACR2-deleted viruses. 21,[37][38][39][40] The additional E1B19K deletion also attenuates viral replication in normal cells through abortive replication in response to extrinsically induced apoptosis. 28,29,35,36 Therefore, the double-deleted AdDD mutant has two viral functions deactivated to prevent amplification in normal tissue while potent replication and spread can proceed in pancreatic tumors that frequently have both deregulated cell cycle and apoptosis pathways.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Treatment to glioma with Ad-Δ24 or its derivatives has been observed to enhance when combined with TRAIL, [16] adenovirus expressing p53, [22] temozolomide, [23] radiation [24] and topoisomerase I inhibitor irinotecan. [25] Autophagic induced cell death and induction of apoptosis are well-characterized results of Ad-Δ24 infection giving the erratum for combination treatments. [26] ANTITUMOR IMMUNE RESPONSE Another important aspect of oncolytic virotherapy is the induction of augmented antitumor immune response.…”
Section: Combination Treatmentsmentioning
confidence: 99%
“…50 Equally, the combination of Delta-24 with irinotecan (CPT-11) showed an enhanced anticancer effect, suggesting that Delta-24 could sensitize glioma cells to the topoisomerase I inhibitor irinotecan. 51 Delta-24-RGD, in combination with everolimus (RAD001), resulted in an enhanced antiglioma effect in vivo via autophagy and increased long-term survival of glioma-bearing animals. 52 Combination of ICOVIR-5 with RAD001 or TMZ showed a potent antiglioma effect both in vitro and in vivo in athymic mice bearing glioma xenografts.…”
Section: Oncolytic Viruses and Chemotherapymentioning
confidence: 99%